2011
DOI: 10.1007/s12192-011-0276-4
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the protective effects of betaine against oxidative damage during experimentally induced restraint stress in Wistar albino rats

Abstract: Stress can be defined as physical and psychological modifications that disrupt the homeostasis and the balance of organisms. Stress is known as one of the most important reasons of several diseases. In the present study, the anti-stress effect of betaine was evaluated with reference to its antioxidant property. Wistar albino rats were divided into four groups such as control, betaine, restraint stress (6 h/day for 30 days), and betaine+restraint stress. The oxidative damage was assessed by measuring the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 48 publications
(44 reference statements)
1
40
0
3
Order By: Relevance
“…Many researchers [29] stated that exposure to stress stimulates various pathways leading to increased production of free radicals that contribute to the occurrence of pathological conditions. Immobilization stress may also impair the antioxidant defense system, leading to oxidative damage, by disturbing the balance between oxidant and antioxidant factors.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers [29] stated that exposure to stress stimulates various pathways leading to increased production of free radicals that contribute to the occurrence of pathological conditions. Immobilization stress may also impair the antioxidant defense system, leading to oxidative damage, by disturbing the balance between oxidant and antioxidant factors.…”
Section: Discussionmentioning
confidence: 99%
“…Choline is oxidized into betaine in a two-step enzyme-dependent reaction in liver and kidney. Betaine is involved in the synthesis of methionine, which acts as a major supplier of cellular cysteine through transsulfuration pathway for the synthesis of reduced glutathione which protects the cell from reactive oxygen species [6]. In choline-mediated one-carbon metabolism, signaling functions, cell membrane structural integrity, and neurotransmitter synthesis betaine plays a major role.…”
Section: Betaine In Lung Cancermentioning
confidence: 99%
“…In choline-mediated one-carbon metabolism, signaling functions, cell membrane structural integrity, and neurotransmitter synthesis betaine plays a major role. Betaine is proved to be safe at a daily intake of dosage 9-15 g [6] which should not exceed. Betaine is nontoxic at all doses (0-5% of the diet) which has determined from subacute and subchronic rat studies.…”
Section: Betaine In Lung Cancermentioning
confidence: 99%
“…The same authors have also reported that superoxide dismutase (SOD) and catalase activities are similar in the thymus and spleen of normal adult rats, although glutathione peroxidase (GPX) activity is slightly higher in the spleen than in the thymus. 9,10 In contrast, Ganesan et al 11 have shown in normal adult rats that GSH and LPO levels and catalase and GPX activities are similar in the thymus and spleen, while SOD and glutathione S-transferase activities are lower in the thymus than in the spleen. Vitamin E is an important antioxidant to break the chain reaction of lipid peroxidation in cellular membranes.…”
mentioning
confidence: 92%
“…14 A recent report has shown that chronic exposure of adult rats to restraint stress (6 hours/day for 30 days) induces oxidative damage in the thymus and spleen through reductions of GSH level and SOD, catalase, GPX, and glutathione S-transferase activities and an increase in LPO level in the those tissues with an increase in serum corticosterone level. 11 To the best of our knowledge, however, there is no information on whether and how a single exposure of adult rats to WIRS as acute stress induces oxidative stress in the thymus and spleen.…”
mentioning
confidence: 99%